2000
DOI: 10.1111/j.1572-0241.2000.03278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Erythromycin on Human Esophageal Motility Is Mediated by Serotonin Receptors

Abstract: Erythromycin exerts its prokinetic action on the lower esophagus by stimulating cholinergic pathways. This action includes not only an increase in LES pressure, but significant increases in the amplitude and duration of esophageal peristalsis, as well. 5-HT3 receptors are also involved in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 18 publications
0
24
0
3
Order By: Relevance
“…50,51 Several prokinetic drugs have shown an increase in amplitude of primary and secondary peristaltic oesophageal contractions, probably because of indirect cholinergic stimulation. 11,12,14,52 More recently, excitation of the afferent pathway by stimulating capsaicin receptors improved the motor performance of the oesophageal body in patients with IOM. 53 In the process of developing treatment strategies in GERD, testing the potential reversibility of IOM in patients with oesophagitis could be useful to predict the response of these patients to new prokinetic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50,51 Several prokinetic drugs have shown an increase in amplitude of primary and secondary peristaltic oesophageal contractions, probably because of indirect cholinergic stimulation. 11,12,14,52 More recently, excitation of the afferent pathway by stimulating capsaicin receptors improved the motor performance of the oesophageal body in patients with IOM. 53 In the process of developing treatment strategies in GERD, testing the potential reversibility of IOM in patients with oesophagitis could be useful to predict the response of these patients to new prokinetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in prevalence of hiatal hernia among GERD patients without IOM (71%), mild IOM (61%) and severe IOM (59%). Patients with hiatal hernia had higher number of supine reflux events [18 (11-27) vs. 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21); P = 0.004] and oesophageal acid exposure [8.3% (3.4-16.1%) vs. 5% (1.4-13.4%); P = 0.020] compared with patients without hiatal her- nia. The LOS pressure was similar in patients with GERD without IOM [10 mmHg (7-13 mmHg)] and patients with mild IOM [9 mmHg (5-12.5 mmHg)].…”
Section: Relationship Between Severity Of Iom Presence Of Hiatal Hermentioning
confidence: 99%
See 1 more Smart Citation
“…Erythromycin acts by stimulating motilin receptors in the upper gastrointestinal tract 55. 5HT3 receptors may also be involved in this process 63. There are no data for its use in palliative care, but it has been shown to be effective in diabetic gastroparesis 64.…”
Section: Drugs For Treating Nausea and Vomitingmentioning
confidence: 99%
“…showed that the gastric phase III‐like migrating contractions, induced by an erythromycin derivative (EM574) in dogs, were the result of the stimulation of vagal cholinergic neurones, where 5‐HT 3 receptors are also involved 22 . In addition, we have recently shown that, in addition to cholinergic pathways, serotonin receptors are involved in the prokinetic effect of erythromycin on oesophageal motility in humans 23 . Based on the aforementioned observations, the first aim of this study was to test the hypothesis that 5‐HT 3 receptors are involved in the acceleration of gastric emptying after erythromycin administration in humans.…”
Section: Introductionmentioning
confidence: 99%